Fenomena Cancel Culture di Platform X dalam Perspektif Hadis Satr Al-‘Aib - Bolamba, Sri Muliawati; Rahma Rizqina Sifa'ul Jayyidah; Meuthya Helena; Nurul Budi Murtini (Rayah Al-Islam, 2026)
The phenomenon of cancel culture on social media has increasingly developed alongside growing public participation in digital spaces, with platform X becoming a space for public judgment against individuals or groups perceived to have committed certain violations. This study aims to identify the forms and characteristics of public judgment in cancel culture practices, examine the concept of satr al-‘aib based on the hadiths in Ṣaḥīḥ Muslim and scholarly commentaries, and analyze its relevance in the context of social media. Employing a qualitative method with a content analysis approach, this study examines three cancel culture cases on platform X during August–December 2025, complemented by an analysis of hadiths and scholarly commentaries. The findings reveal that cancel culture is characterized by mass mobilization through hashtags, public pressure, collective judgment without verification, personal attacks, and diverse user responses. The analysis demonstrates that satr al-‘aib is not an absolute principle but has specific limits and conditions aimed at preserving welfare and preventing harm. It rejects unverified judgments, excessive actions, and humiliation while allowing proportionate and fact-based criticism. This study contributes by integrating social media content analysis with a hadith perspective to formulate ethical boundaries for public judgment. The findings highlight Islamic communication ethics as a normative framework for fostering a more just and responsible digital space.